Documentation IZAΨMOD: The IZA policy sImulation mODel - Andreas Peichl; Hilmar Schneider; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2010)
This paper describes IZAΨMOD, the policy microsimulation model of the Institute for the Study of Labor (IZA). The model uses household microdata from the German Socio-Economic Panel Study and firm data from the German linked employer-employee dataset LIAB. IZAΨMOD consists of three components: First, a static module simulates the effects of a tax reform on the budget of the individual households. Secondly, behavioral labor supply responses are estimated. The third component distinguishes our model from most other microsimulation tools. A demand module takes into account possible restrictions of labor demand and identifies the partial equilibrium of the labor market after the supply reactions.
Keywords: D58; H20; J22; J23; 330; IZAΨMOD; microsimulation; tax and benefit systems; labor demand; Mikrosimulation; Steuersystem; Sozialtransfer; Arbeitsnachfrage; Arbeitsangebot; Theorie